2017
DOI: 10.1038/s41598-017-06555-8
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Solid Electrolyte Interphase Structure Grown on a Silicon Electrode Using a Fluoroethylene Carbonate Additive

Abstract: In this work we explore how an electrolyte additive (fluorinated ethylene carbonate – FEC) mediates the thickness and composition of the solid electrolyte interphase formed over a silicon anode in situ as a function of state-of-charge and cycle. We show the FEC condenses on the surface at open circuit voltage then is reduced to C-O containing polymeric species around 0.9 V (vs. Li/Li+). The resulting film is about 50 Å thick. Upon lithiation the SEI thickens to 70 Å and becomes more organic-like. With delithia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
170
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(187 citation statements)
references
References 64 publications
12
170
1
Order By: Relevance
“…A discrepancy is also found in the SLD of the SEI that is ranging between 2 Â 10 À6 Å À2 and 4 Â 10 À6 Å À2 in the work of Veith et al 22 compared to values found here of 0.4 Â 10 À6 Å À2 to 1.2 Â 10 À6 Å À2 . In a different study 24 of the same group, where fluorinated ethylene carbonate was used as an additive to the electrolyte, also a thickening of the SEI was found during lithiation by some tenths of a nanometre and a reduction during delithiation, in qualitative agreement with our work. Fears et al 23 found by NR and X-ray photoelectron spectroscopy (XPS) also SEI growth and shrinkage during electrochemical cycling.…”
Section: Further Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…A discrepancy is also found in the SLD of the SEI that is ranging between 2 Â 10 À6 Å À2 and 4 Â 10 À6 Å À2 in the work of Veith et al 22 compared to values found here of 0.4 Â 10 À6 Å À2 to 1.2 Â 10 À6 Å À2 . In a different study 24 of the same group, where fluorinated ethylene carbonate was used as an additive to the electrolyte, also a thickening of the SEI was found during lithiation by some tenths of a nanometre and a reduction during delithiation, in qualitative agreement with our work. Fears et al 23 found by NR and X-ray photoelectron spectroscopy (XPS) also SEI growth and shrinkage during electrochemical cycling.…”
Section: Further Analysissupporting
confidence: 91%
“…Before further analysis of the experimental data is done, the following point has to be stated: we assumed in our model a spatial constant Li concentration x within the a-Li x Si layer (homogenous Li distribution) where x increases with lithiation time and decrease with delithiation time as also done by other authors. 22,24 This model assumption is not a priori valid. Also a spatial heterogeneous Li distribution in the a-Li x Si layer might be present at least during initial stages of the first cycle during galvanostatic cycling.…”
Section: View Article Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…[13] An alternative approach to study surfaces which are not transparent to neutrons, is to support a thin film of the material on a transparent substrate. This has been reported for an increasing number of metal systems including Fe [14,15], Ti [16][17][18], Cu [19][20][21][22][23][24][25], Ni [26][27][28], Al [29,30] and Au [31][32][33][34]. Steel [35] remains a challenge with the overall deposited composition replicated, but the metallurgical aspects are not necessarily typical of bulk steel (see section 2.3 below).…”
Section: Solid Substratesmentioning
confidence: 94%
“…NR has been used to identify a number of characteristics of the SEI including irreversible Li incorporation, [25] formation of a "skin",[57] the report of a "breathing" mode [24] and the important role of additives [23], with precise details depending on the electrode and electrolyte used. Importantly there are discrepancies between these in-situ NR measurements and complementary ex-situ XPS data.…”
Section: Electrochemistrymentioning
confidence: 99%